Morphology and Development of Several External Myiasis Larvae Recorded in Elazi? - Şaki, Cem Ecmel; Özer, Edip (My University, 1999)
A study was conducted on external myiasis of livestock in Elazi? and its districts (Sivrice, Kovancilar, Baskil and Salkaya) in 1994-1995. Eight species of myiasis flies including Lucilia sericata, L. caesar, Calliphora vicina, C. vomitoria, Chrysomya albiceps, Wohlfahrtia magnifica, Sarcophaga haemorrhoidalis and S. carnaria were determined and published seperately. In addition, morphological and biological characteristics of larvae of Lucilia sericata, Calliphora vicina, Wohlfahrtia magnifica and Sarcophaga haemorrhoidalis were investigated under laboratory conditions as well. The studies showed that development from larvae to fly was recognized in 17-22 days for L. sericata, 10-16 days for S. haemorrhoidalis, 19-23 days for C. vicina and W. magnifica. The morphological characteristics of the larvae in different phases were described in detail in this paper.
Elazi? ve Çevresinde Tespit Edilen Eksternal Myiasis Larvalarinin Morfoloji ve Gelişmeleri
Keywords: Biology; External Myiasis; Larvae; Morphology